EVALUASI OPERASIONAL SIMPANG BUNDARAN SAMSAT KOTA YOGYAKARTA BERDASARKAN MANUAL KAPASITAS JALAN INDONESIA 1997 - , KUSNAN MUDDARIS SULTHONI MUFTI, Suwardo, ST., MT., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There is intersection along with road segment. The crossing point of the four- way traffic flow is called the intersection or roundabout. Traffic control at the roundabout intersection is the most critical and important in the overall movement of traffic on the road network in the city . The purpose of this study was to determine capacity of the roundabout intersection area and to evaluate performance of roundabout. The standard used in this study is the standard Indonesian Highway Capacity Manual 1997. The experiment was conducted at the roundabout intersection of Samsat yogyakarta City. The tools used in survey include stationery, cameras, counter, meter, and stopwatch than Microsoft Excel as a tool to analyze the data. After indepth analysis of the survey results on Monday shows the level of capacity ( C ) is 10541,013 pcu/hour to BC, the largest value of DS on Monday was 0,919 for weaving area AB, the highest number of total vehicle volume is 51902 and the average volume of 6920 veh/hour on the May 13, 2013 while the traffic delays that occur on May 13, 2013 was 16.899 sec/pcu and average delay - the average is 20.899 sec/pcu, the biggest queue for opportunities on May 13, 2013 is the weaving area AB that is 29 - 62 %. Thus obtained the performance of traffic flow on Monday, May 13, 2013 is more dense than the performance of the traffic flow on Wednesday, May 15, 2013.